1D to 3D multi-stable architected materials with zero Poisson's ratio and controllable thermal expansion. (March 2020) - Yang, Hang; Ma, Li
Abstract: Multi-stable mechanical metamaterials with unprecedented mechanical/physical properties have attracted great interests due to their functional applications for advanced materials and devices. However, the original curved/tilted bistable snapping segments in most of those existing multi-stable mechanical metamaterials cause unequal bistability/multi-stability. The relative thicker supporting segments can't provide complete constraints at the end of snapping segments using single parent material. To achieve completely symmetric bistable/multi-stable mechanism, an innovative design strategy is proposed based on interlocking assembly method with multi-materials and compressed buckled snapping segments for bistable units. Theoretical analysis, numerical simulations and experimental verifications are used to show completely symmetric bistability/multi-stability with negative stiffness. The multi-stable mechanical metamaterials have robust shape-reconfigurability and zero Poisson's ratio with large recoverable deformation. Geometric and material gradients design are carried out to control deterministic deformation sequence with rich programmability. Theoretical and numerical results reveal that tunable 1D to 3D large positive/zero/negative isotropic or anisotropic thermal expansions of single 1D to 3D multi-stable metamaterials can be achieved, respectively. This work suggests the rational designed metamaterials with multi-abnormal-index and the potential applications of multi-functional metamaterials. Graphical abstract: Unlabelled Image Highlights: 1D to 3D multi-stable mechanical metamaterials are fabricated by assembly method with multi-materials. Robust shape-reconfigurability and zero Poisson's ratio are achieved with large recoverable deformation. Geometric and material gradients design are proposed to control deterministic deformation sequence. Tunable 1D to 3D positive/zero/negative thermal expansions are achieved based on multi-stable mechanism.